Social representations of environmental practices of the instructors that guide the competition of Institutional Policy in the Agroindustrial Technologies Center of Cartago, SENA Valle - Gómez Pérez, Alejandro
The present study aimed to identify the social representations of environmental practices that have the instructors that guide the institutional competence in Centro de Tecnologías Agroindustriales de Cartago-SENA Regional Valle del Cauca. It is a qualitative research with a descriptive study. The population was made up of 6 instructors who guide the institutional policy competence of SENA. A semi-structured interview was applied to obtain the different social representations about the orientation of environmental practices in the entity. The study allowed the identification of social representations of environmental practices, where the development of environmental concepts, compliance with Colombian legislation and regulations, management of raw materials, solid waste management, interpretation of environmental problems, corporate environmental responsibility, saving water and the application of sustainable actions in the business and social environment.